2004
DOI: 10.1038/nmat1056
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-stable nanoparticles of CdSe revealed from mass spectrometry

Abstract: Nanoparticles under a few nanometres in size have structures and material functions that differ from the bulk because of their distinct geometrical shapes and strong quantum confinement. These qualities could lead to unique device applications. Our mass spectral analysis of CdSe nanoparticles reveals that (CdSe)(33) and (CdSe)(34) are extremely stable: with a simple solution method, they grow in preference to any other chemical compositions to produce macroscopic quantities. First-principles calculations predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

97
744
11
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(856 citation statements)
references
References 10 publications
97
744
11
4
Order By: Relevance
“…This lack could be due to their relatively low stability in comparison to other magic-sized nanocrystals such as (CdSe)13 and (CdSe)33/34. 60,63 It should be mentioned that the broadness of the LDI-MS peak (covering 5.5-7.5 kDa) could be due to formation of other MSNs during the laser ablation as had earlier been reported. 60 Until now the literature have reported that exclusive formation of single-sized MSNs such as (CdSe)13, (CdSe)34, or (CdSe)56 has only been observed at room temperature.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…This lack could be due to their relatively low stability in comparison to other magic-sized nanocrystals such as (CdSe)13 and (CdSe)33/34. 60,63 It should be mentioned that the broadness of the LDI-MS peak (covering 5.5-7.5 kDa) could be due to formation of other MSNs during the laser ablation as had earlier been reported. 60 Until now the literature have reported that exclusive formation of single-sized MSNs such as (CdSe)13, (CdSe)34, or (CdSe)56 has only been observed at room temperature.…”
Section: Resultsmentioning
confidence: 73%
“…60 Until now the literature have reported that exclusive formation of single-sized MSNs such as (CdSe)13, (CdSe)34, or (CdSe)56 has only been observed at room temperature. 41,60,63 Upon heating these nanocrystals at moderately high temperature (>100 0 C), RNCs were formed, which is due to destabilization of MSNs by overcoming the energy barrier. Figure 2B shows the UV-vis spectra of the our reaction mixture containing (CdSe)19 nanocrystals at 60 0 C. Interestingly, with time not only did the band-edge peak red-shift but also the peak intensity decrease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magic numbers for the (CdSe) n clusters (n = 13, 33, and 34) were revealed by mass spectroscopy [7]. These building blocks play a role in constructing the NCs of interest.…”
Section: Introductionmentioning
confidence: 99%
“…CdSe nanoparticles were prepared by a wet chemical method in reverse micelles put in toluene [12,13] following injection of toluene. Once the toluene is added to this solution, the micelles move up into the toluene and transform into reverse micelles, in which nucleation and further growth of nanoparticles takes place at the temperatures higher than 45˚C.…”
Section: Methodsmentioning
confidence: 99%